Morphological alterations of the cornea following crosslinking treatment (CXL). Issue 6 (23rd February 2021) - Subasinghe, Sandeepani K.; Ogbuehi, Kelechi C.; Mitchell, Logan; Dias, George J.
Abstract: Introduction: Corneal crosslinking (CXL) has revolutionized the treatment of keratoconus during the past decade. In the present study, the morphological changes in the corneal collagen fibrils (CFs) following crosslinking treatment are described. Materials and Methods: Ten pairs of porcine and rabbit corneas were retrieved. In each pair, one cornea was the control and the other underwent CXL treatment. The central corneal thickness (CCT) was measured before and after CXL treatment. Each treated and control cornea was examined with light microscopy and by transmission electron microscopy. Results: (a) The mean CCT was significantly reduced following treatment. (b) CFs were more closely packed in the anterior region and loosely packed in the posterior region. (c) CF diameter increased significantly in the anterior and intermediate regions but declined gradually towards the deeper regions. (d) There was a statistically significant decrease in the interfibrillar distance over the different regions of the cornea, except for the posterior region in porcine corneas, where there was no change. (e) The distance between adjacent collagen lamellae was significantly decreased in all regions of treated rabbit corneas. There was no change in porcine corneas. Conclusion: CXL treatment resulted in increased the CF diameter and decreased interfibrillar distance in the anterior and intermediate regions, while its effects on the posterior region differed among species. The effect on interlamellar distance was more prominent in the rabbit model than the porcine model. CXL treatment stiffened the corneas by increasing CF diameter and decreasing interfibrillar distance in both rabbit and pig corneas.